Desingularization and Dequalification: A Foray Into Ranking Production and Utilization Processes. Issue 4 (8th August 2019) - Picard, Claire-France; Durocher, Sylvain; Gendron, Yves
Abstract: Although some authors highlight the benefits of journal rankings, previous research is often highly critical of them, insinuating that they can lead to desingularization of academic journals (i.e. their impoverishment and standardization) and dequalification of researchers (i.e. a weakening of researchers' ability to evaluate academic research). However, as very few authors have empirically assessed these presumptions, we aim to address this gap in the literature. Based on Lucien Karpik's notions of singularities, judgment devices, forms of involvement, and emulation and rivalry, we assess whether the processes surrounding the production and use of journal rankings might lead to desingularization and dequalification. Our findings support previous research by highlighting that processes where passivity and heteronomy (i.e. lack of autonomy) prevail are conducive to desingularization, rivalry and dequalification. Our findings, however, introduce some nuances into the debate by underscoring instances where emulation logic is employed instead of mere rivalry logic, and where substantial judgment devices and active involvement are mobilized in the production and use of rankings, thereby somewhat alleviating the spread of desingularization and dequalification. Ultimately, our study raises questions that point to a need for serious collective reflection within the academic community on the processes by which published research is evaluated.